Dignity therapy in Mexican lung cancer patients with emotional distress: Impact on psychological symptoms and quality of life. Issue 1 (February 2022) - Gonzalez-Ling, Ana; Galindo Vázquez, Oscar; Rascón-Gasca, María Luisa; Robles, Rebeca; Chochinov, Harvey Max
Abstract: Lung cancer (LC) is the most frequent and deadly neoplasm in the world, and patients have shown a tendency to have more emotional distress than other cancer populations. Dignity Therapy (DT) is a brief intervention aimed to improve emotional well-being in patients facing life-threatening illness. Objective: To analyze the effect of DT on anxiety, depression, hopelessness, emotional distress, dignity-related distress, and quality of life (QoL) in a group of Mexican patients with stage IV LC undergoing active medical treatment with baseline emotional distress. Method: In this preliminary pretest–posttest study, patients received three sessions of DT and were evaluated with the HADS, Distress Thermometer, Patient Dignity Inventory, single-item questions, and QLQ-30. Results: In total, 24 out of 29 patients completed the intervention. Statistically significant improvements were found in anxiety, depression, emotional distress, hopelessness, and dignity-related distress with large effect sizes. Patients reported that DT helped them, increased their meaning and purpose in life, their sense of dignity, and their will to live, while it decreased their suffering. No changes were found in QoL. Significance of results: DT was well accepted and effective in improving the emotional symptoms of LC patients with distress that were undergoing medical treatment. Although more research is warranted to confirm these results, this suggests that DT can be used in the context of Latin-American patients.